2023
DOI: 10.1063/5.0136719
|View full text |Cite
|
Sign up to set email alerts
|

Where are the coexisting parallel climates? Large ensemble climate projections from the point of view of chaos theory

Abstract: We review the recent results of large ensemble climate projections considering them to be the simulations of chaotic systems. The quick spread of an initially localized ensemble in the first weeks after initialization is an appearance of the butterfly effect, illustrating the unpredictability of the dynamics. We show that the growth rate of uncertainty (an analog of the Lyapunov exponent) can be determined right after initialization. The next phase corresponds to a convergence of the no longer localized ensemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It is worth noting that a climate model can only be credible if it is converged to the snapshot attractor of the climate (Deser, 2020;Herein et al, 2023). Previous studies show that the convergence time is approximately 40 years in PlaSim (Drótos et al, 2017;Drótos and Bódai, 2022), and similar values are found for more complex climate models, too (Drótos and Bódai, 2022).…”
Section: Model Convergencementioning
confidence: 63%
See 3 more Smart Citations
“…It is worth noting that a climate model can only be credible if it is converged to the snapshot attractor of the climate (Deser, 2020;Herein et al, 2023). Previous studies show that the convergence time is approximately 40 years in PlaSim (Drótos et al, 2017;Drótos and Bódai, 2022), and similar values are found for more complex climate models, too (Drótos and Bódai, 2022).…”
Section: Model Convergencementioning
confidence: 63%
“…The black line corresponds to the measured, observed global mean surface temperature. The fact that the black curve is within the gray band of the ensemble and convergence is reached as discussed in (Herein et al, 2023) illustrates that PlaSim can be considered a credible model (Deser, 2020;Tokarska et al, 2020;Suárez-Gutiérrez et al, 2021). Our simulations reported below are carried out with this PlaSim setup.…”
Section: Figurementioning
confidence: 93%
See 2 more Smart Citations